CORPORATE GOVERNANCE, WHISTLE BLOWING POLICY DAN EARNINGS MANAGEMENT PADA PERUSAHAAN JASA DI INDONESIA - Dian Indriana Hapsari (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2020)
Corporate Governance mechanisms are not able to effectively mitigate Earnings Management. Whistleblowing Policy can play a role in carrying out effective functional governance so that it is expected to be able to reduce Earnings Management activities significantly. This study aims to examine whether the corporate governance mechanism in a company that implements Whistleblowing Policy is more effective in limiting Earnings Management than companies that do not implement Whistleblowing Policy. The study method used is descriptive-associative. The sample in this study was manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. This research results in findings that the Corporate Governance mechanism is more effective in companies that have a Whistleblowing Policy than companies that do not have a Whistleblowing Policy. The flow of information before the Whistleblowing Policy occurs a significant effect. Likewise, company size and leverage also have a substantial impact on Earnings Management. Meanwhile, there is no effect on the number of independent commissioners on Earnings Management.